PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN SOLEAR KABUPATEN TANGERANG - Ika Yuliasuti; Bunga Astra Gracia (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the Leadership Style and Work Discipline on the Performance of Employees at the Solear District Office, Tangerang Regency partially and simultaneously. The research method used was a quantitative method, with questionnaire data collection techniques and secondary data with non-probability sampling techniques with saturated sampling techniques. The population and samples taken were 51 people. The results of the study based on the t-test, it is known that the value of the Leadership Style variable (X1) is 4.673 and the t-table data is 2.010 (Df = n-k-1) so (51-2-1 = 48) then it can be concluded that Ho is rejected and Ha is accepted, meaning that the Leadership Style variable (X1) partially has a significant influence on Employee Performance (Y) at the Solear District Office, Tangerang Regency. It is known that the value of the Work Discipline variable (X2) is 8.273 and the t table is 2.010 (Df = n-k-1) so (51-2-1 = 48) and is also supported by the calculated t> t table. So it can be concluded that H0 is rejected Ha is accepted, meaning that the Work Discipline variable (X2) partially has a significant effect on Employee Performance (Y) at the Solear District Office, Tangerang Regency. It is known again that the basis for the measurement is the calculated f value> f table, the results obtained are (33.524> 2.010) with a p value score <Sig. 0.05 which in this study (0.000 <0.05 then the last is H3 in the study is accepted and H0 is rejected which in this study has a significant impact on the independent variable on Employee Performance at the Solear District Office, Tangerang Regency. Based on the quantitative analysis of multiple regression, it was concluded that Y = 8.082 + 0.823X1 + 0.168X2 from the results of the multiple linear regression analysis, it was obtained that the variables of Leadership Style (X1) and Work Discipline (X2) had a linear effect on Employee Performance (Y), and at the correlation coefficient value R of 0.763, it can be concluded that the value is in the range of 0.600 to 0.799, so the level of relationship between the variables of Leadership Style (X1) and Work Discipline (X2) on Employee Performance (Y) there is a strong level of relationship. The R result obtained was 0.763, so in this case it was concluded that the variables of Leadership Style (X1) and Work Discipline (X2) had an effect on Employee performance (Y) is 58.3% while 4.7% is influenced by other factors